Two new cobalt(II) rhodamine 6G hydrazone complexes: structure, fluorescence and magnetism. Issue 12 (13th November 2018) - Yuan, Juan; Wang, Xia; Zhang, Nan; Liu, Mei-Jiao; Kou, Hui-Zhong
Abstract : Rhodamine 6G‐labelled hydrazone Co II complexes with an N4 O2 donor set show intermolecular π–π stacking interactions between xanthene moieties to form a supramolecular one‐dimensional chain structure. The ring‐opened rhodamine 6G ligands are responsible for a green fluorescence and the temperature‐dependent magnetic susceptibilities of the complexes are dominated by the structural distortion and spin‐orbit coupling of Co II . Abstract : Two new Co II complexes, namely bis N ‐[(6‐bromopyridin‐2‐yl)methylidene]‐2‐[6‐ethylamino‐3‐(ethyliminiumyl)‐2, 7‐dimethyl‐3 H ‐xanthen‐9‐yl]benzene‐1‐carbohydrazonatecobalt(II) bis(perchlorate)–dichloromethane–methanol (1/1/2), [Co(C32 H30 BrN5 O2 )2 ](ClO4 )2 ·CH2 Cl2 ·2CH3 OH or [Co II (L )2 ](ClO4 )2 ·CH2 Cl2 ·2CH3 OH, (1), and the bis(tetrafluoridoborate) salt, [Co(C32 H30 BrN5 O2 )2 ](BF4 )2 ·CH2 Cl2 ·2CH3 OH or [Co II (L )2 ](BF4 )2 ·CH2 Cl2 ·2CH3 OH, (2) (L is commonly 6‐bromopyridine‐2‐carbaldehyde rhodamine 6G hydrazone), have been successfully constructed and characterized. The crystal structure analysis revealed that complexes (1) and (2) are mononuclear and have a Co II N4 O2 distorted octahedral structure. The large π‐conjugated xanthene moiety of theL ligand causes strong intermolecular π–π stacking interactions, yielding a supramolecular one‐dimensional chain. Complexes (1) and (2) display an obvious fluorescence emission near 560 nm in the solid state. Magnetic investigations show that both (1) and (2) are paramagnetic, dominated by the structural distortion and spin‐orbit coupling of Co II .